2023
DOI: 10.1111/pde.15421
|View full text |Cite
|
Sign up to set email alerts
|

Risk for second primary cancers among pediatric and young adult melanoma survivors

Yen Luu,
Joseph Han,
Aneesh Agarwal
et al.

Abstract: Background/ObjectivesSecond primary cancers (SPCs) are a leading cause of morbidity and mortality among cancer survivors. In this study, we aimed to characterize the incidence of SPCs among pediatric and young adult survivors of CM.MethodsUsing the Surveillance, Epidemiology, and End Results Program data spanning 2000–2018, we calculated standardized incidence ratios (SIR) to assess SPC risk in all pediatric (0–18 years) and young adult (19–29 years) patients with a first primary cancer diagnosis of CM.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Elisabetta Magnaterra MD 1 Biancamaria Zuccaro MD 1 Manfredi Magliulo MD 1 Federico Venturi MD 1 Gabriella Perillo MD 1 Massimo Gola MD 1 Vincenzo De Giorgi MD…”
Section: Funding Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Elisabetta Magnaterra MD 1 Biancamaria Zuccaro MD 1 Manfredi Magliulo MD 1 Federico Venturi MD 1 Gabriella Perillo MD 1 Massimo Gola MD 1 Vincenzo De Giorgi MD…”
Section: Funding Informationmentioning
confidence: 99%
“…leagues. 1 In this study, the authors found that 8.82% of 7169 survivors of cutaneous melanoma developed second primary cancers (SPCs) with a nearly five-fold risk compared to the general population.…”
mentioning
confidence: 96%